What Puts Individuals at Risk for Physical Intimate Partner Violence Perpetration? A Meta-Analysis Examining Risk Markers for Men and Women. (January 2022) - Spencer, Chelsea M.; Stith, Sandra M.; Cafferky, Bryan
Intimate partner violence (IPV) perpetration is a serious public health concern around the world. This meta-analysis aimed to synthesize all available data examining risk markers for physical IPV perpetration among men and women between 1980 and 2018. Studies were included in the analysis if they examined physical IPV in adult opposite-sex relationships, included statistical information needed to calculate at least one bivariate effect size, and were written in English. A total of 503 studies, yielding 2, 972 unique effect sizes, were included in the analysis. Data from these studies allowed for the examination of 63 unique risk markers related to physical IPV perpetration for both men and women, 60 unique risk markers for male perpetration, and 45 unique risk markers for female perpetration. Lastly, we were able to compare the strength of 44 risk markers for physical IPV perpetration between men and women. We found that the strongest risk markers were related to other acts of violence (both perpetration and victimization) as well as relationship dynamics. Results from this study highlight the potential factors that could be focused on in prevention programming and intervention work. Additionally, it was found that 9 out of 44 risk markers significantly differed in strength for men and women, allowing for additional specificity in intervention work for helping professionals working with either male or female perpetrators of physical IPV.